2023
DOI: 10.3390/ijms24076213
|View full text |Cite
|
Sign up to set email alerts
|

A PCOS Paradox: Does Inositol Therapy Find a Rationale in All the Different Phenotypes?

Abstract: A recent evaluation of the published data regarding the PCOS topic has highlighted a paradox in the definition of this condition. Even though the name of the syndrome refers to ovarian dysfunction, it seems that patients diagnosed with PCOS are more likely affected by an endocrine and metabolic issue. The term PCOS might not be appropriate to indicate the phenotypes described by the Rotterdam criteria, since the only phenotype with a gynecological issue alone is PCOS phenotype D. This novel perspective regardi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 54 publications
(52 reference statements)
0
11
0
1
Order By: Relevance
“…Decreased endometrial Glut4 gene expression is also regulated by ARs through binding to the GLUT promoter in rat models ( 15 ). Interestingly, one three-dimensional culture of mouse follicles in vitro demonstrated that high concentrations of insulin-like growth factor-1 (IGF-1) could inhibit mouse follicular development and maturation, which provides a possible explanation for the involvement of IGF-1 in the pathogenesis of ovulatory disorders in phenotype D in the absence of HA ( 2 , 16 ). Moreover, enhanced CYP17 activity in TCs is regulated by the PI3K/AKT pathway ( 17 ).…”
Section: Insulin Resistancementioning
confidence: 99%
See 1 more Smart Citation
“…Decreased endometrial Glut4 gene expression is also regulated by ARs through binding to the GLUT promoter in rat models ( 15 ). Interestingly, one three-dimensional culture of mouse follicles in vitro demonstrated that high concentrations of insulin-like growth factor-1 (IGF-1) could inhibit mouse follicular development and maturation, which provides a possible explanation for the involvement of IGF-1 in the pathogenesis of ovulatory disorders in phenotype D in the absence of HA ( 2 , 16 ). Moreover, enhanced CYP17 activity in TCs is regulated by the PI3K/AKT pathway ( 17 ).…”
Section: Insulin Resistancementioning
confidence: 99%
“…Patients should be thoroughly assessed to exclude other conditions that cause symptoms similar to PCOS. Although approximately 75% of patients with PCOS exhibit insulin resistance (IR), IR is not recognized as a diagnostic criterion ( 2 ).…”
Section: Introductionmentioning
confidence: 99%
“…This is mirrored in patient populations, as 50-80% of women with PCOS are affected by IR [2,3], 61% are overweight/obese [4], and >50% suffer from type 2 diabetes mellitus and metabolic syndrome before the age of 40 [5]. Moreover, it has been widely discussed that PCOS-associated hyperandrogenism and reproductive problems, may be a consequence of metabolic disorders, and thus have been defined as "metabolic hyperandrogenism" by some members of the field [6]; therefore, PCOS may be more accurately described as "metabolic reproductive syndrome," as defined previously by the National Institutes of Health (NIH) evidence-based methodology workshop of PCOS 2012 [7]. At the same time, elevated androgen levels intern promotes the accumulation and redistribution of adipose tissue in women, causing damage to insulin signaling pathways, creating a vicious cycle leading to further impaired glucose metabolism and IR [8].…”
Section: Introductionmentioning
confidence: 99%
“…Insulin may further indirectly affect steroidogenesis by altering the ovarian homeostasis between stereoisomers of inositol in ovarian tissuemyo-inositol (MI) and D-chiro-inositol (DCI) [6]. MI and DCI are secondary messengers of insulin, where MI is responsible for the intracellular glucose transport and is simultaneously converted to DCI, which facilitates glycogen storage.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation